The Effect of Lavender Aromatherapy on Reducing Anxiety in the Context of Nursing Care: A Literature Review - Sembiring, Nur Maghribi; Sembiring, Atikah Marhamah; Sembiring, Muhammad Simba (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Background : Anxiety is a feeling of fear about something that occurs, caused by the anticipation of danger, and serves as a signal that helps individuals prepare to take action in the face of a threat. Lavender is often used in aromatherapy because it can provide relaxation and has a sedative effect that is very helpful for people experiencing excessive anxiety. Relaxation techniques are a way to reduce anxiety. One relaxation technique that can be used is aromatherapy. Aim This study aims to determine the effect of lavender aromatherapy on reducing anxiety levels. Method : The data used in this study are secondary data obtained from previous research. The data sources were articles or journals relevant to this topic. Articles were obtained from 2021-2025. Data searches were conducted using Google Scholar with the keywords